Modified Shuttle Test Distance Correlates With Peak Oxygen Uptake in Children and Adolescents With Severe Therapy-Resistant Asthma - Schiwe, Daniele; Heinzmann-Filho, João Paulo; Schindel, Cláudia Silva; Gheller, Mailise Fátima; Campos, Natália Evangelista; Pitrez, Paulo Márcio; Donadio, Márcio Vinícius Fagundes (Frontiers in Physiology, 2019)
Introduction: Several tests may be used to assess exercise intolerance in severe therapy-resistant asthma (STRA), including the gold standard cardiopulmonary exercise test (CPET) and the Modified Shuttle Test (MST). Objective: To correlate the distance achieved in the MST with peak oxygen uptake (VO2peak) and to compare the maximal heart rate (HRmax) obtained in both tests in children and adolescents with STRA. Methods: This is a cross-sectional study, with nineteen children and adolescents with STRA. Demographic, anthropometric, clinical data and spirometric values were collected. CPET and the MST were performed in two consecutive visits. HRmax, pulse oxygen saturation and dyspnea were compared between tests. The distance achieved in the MST was correlated with VO2peak. Results: Nineteen patients with a mean age of 11.5±2.5 years were included. The mean HRmax (bpm) achieved was 180.8±12.10 for the MST and 187.6±9.35 for CPET, whereas the mean HRmax as a percentage of predicted (HRmax%) was 90.7±6.5 for the MST and 93.8±4.5 for CPET. A difference of only 6 bpm was found for HRmax (p=0.10) and of 3% for HRmax% (p=0.06) between tests. A strong correlation was found between the MST (r=0.79; p˂0.001) and VO2peak measured through CPET. However, there were no correlations between the MST and both body mass index (r=-0.14; p=0.564) and forced expiratory volume in the first second - FEV1 (r=-0.02; p=0.917). Conclusion: The results demonstrate that the MST distance strongly correlates with VO2peak, measured through CPET, and the main physiological variable responses were similar between both tests. Our results provide additional data for the use of the MST to assess exercise capacity in children and adolescents with STRA.